Formulasi Kebijakan Pengelolaan Hutan bersama Masyarakat di Taman Nasional Gunung Ciremai - Farma Yuniandra; Cecep Kusmana; Dodik Ridho Nurrochmat (Jurnal Manajemen Hutan Tropika, 2011)
Implementation of Collaborative Forest Management (CFM) at 25 villages in the Mount Ciremai, Kuningan Regency, West Java Province has became a problem because of specifying as national park.  The objectives of this research were  to analyze policy of CFM, examining implementation and it’s impact in Mount Ciremai National Park,  and  to  formulate  policy strategy of CFM in Mount Ciremai National Park.  Methods of this research were policy analysis, descriptive analysis, AHP,  and SWOT.  Implementation of the CFM policy in  Kuningan Regency  consisted of: socialization, forming of CFM Forum, mapping, inventory, planning of village, NKB, NPK, and village regulation.  Economic impact from the policy of CFM in Kuningan Regency  contributed the income to about 7,71% from the nominal of Rp 3.336.573,- per capita per year and poverty rate after CFM in general was relatively  low.  This research  showed  that CFM policy strategies  that should be  applied in Mount Ciremai National Park were  socialization of economic value of the national park,  regulation’s intervention, developing the utilization of national park,  and empowerment of the community economic.